If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9s + 2 = -16 Reorder the terms: 2 + -9s = -16 Solving 2 + -9s = -16 Solving for variable 's'. Move all terms containing s to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + -9s = -16 + -2 Combine like terms: 2 + -2 = 0 0 + -9s = -16 + -2 -9s = -16 + -2 Combine like terms: -16 + -2 = -18 -9s = -18 Divide each side by '-9'. s = 2 Simplifying s = 2
| 2(1.2x+4)=4(0.6x+1)+1 | | 4x+44-5x=3-7x+5 | | .025x+.74-x=.7 | | 3x-33-4=4x-16 | | 4r+19-8=0 | | 31=20-x | | F(x)=-2(x+3)-5 | | (2a^2-1)(8a-5)= | | 0.6+a=1.3 | | 10=.25(b-11) | | X(15x+11)+2=0 | | 4y-10=2y+5 | | 4x-9=-6+5x | | -4.9t^2+24.5t+2=0 | | 7x+3x-4x=3-3(x+4) | | 139=-5-2(4+8P) | | (5x^3y^2-3xy^5+12x^2)-(-9x^2-8x^3y^2+2xy^5)=0 | | 4x-9=-6+-5x | | 3x(-3)+b= | | 7-3a=11+a | | X(15x+11x)+2=0 | | 4.9t^2-24.5t+2=0 | | c^2-3c-18= | | 6+3(13-2)-25= | | 5x+2-4x=5+8 | | -5y+7y=10 | | 2(4p+3)-3(3p-6)-16p= | | -6(7x-1)=-8x+9(-3x+4) | | .5(4m+5)=-6 | | t^2-24.5t+2=0 | | 2a/3a-3/4=3a/4a | | h(t)=-16t^2+20t+4 |